2022
DOI: 10.3390/bdcc6040140
|View full text |Cite
|
Sign up to set email alerts
|

Physics-Informed Neural Network (PINN) Evolution and Beyond: A Systematic Literature Review and Bibliometric Analysis

Abstract: This research aims to study and assess state-of-the-art physics-informed neural networks (PINNs) from different researchers’ perspectives. The PRISMA framework was used for a systematic literature review, and 120 research articles from the computational sciences and engineering domain were specifically classified through a well-defined keyword search in Scopus and Web of Science databases. Through bibliometric analyses, we have identified journal sources with the most publications, authors with high citations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 114 publications
0
11
0
Order By: Relevance
“…• Recently, many researchers attempted to extend the PINN algorithms to overcome these challenges [172].…”
Section: Discussionmentioning
confidence: 99%
“…• Recently, many researchers attempted to extend the PINN algorithms to overcome these challenges [172].…”
Section: Discussionmentioning
confidence: 99%
“…The use of PINNs is currently being studied as a potential replacement for existing numerical techniques. Due to the recent advent of this type of neural networks, the literature is not yet massive, but reports particularly important pivotal works such as e.g [3,4,5,6,7,8,9,10,11,12,13,14,15,16]. A comprehensive review can be also found in [17].…”
Section: Introductionmentioning
confidence: 99%
“…PINNs are particularly useful in fields where conventional data-driven approaches may fall short due to limited or noisy data. By incorporating biological laws and constraints within the PINN framework, they can effectively solve a range of differential equations, including partial differential equations (PDEs), integral-differential equations, and stochastic PDEs [14], making them highly suitable for studying brain dynamics models (BDMs).…”
Section: Introductionmentioning
confidence: 99%